Current Topics (The Muslim world, 1937)
Across the Sahara The Cross in Islam Hindu and Moslem A Brief Summary of Statements by Representative Moslems regarding Religious Movements in India Indian Outcastes (A letter from Sayyid Ahmad Muhammad Iqbal to the Sheikh of the Azhar) By Air down the Persian Gulf